2019
DOI: 10.21203/rs.2.12428/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Female sex workers perspectives and concerns regarding HIV self-testing: An exploratory study in Tanzania

Abstract: Background: HIV testing is a gateway to HIV care and treatment for those testing positive and can link those with negative results to HIV preventive services. Despite the importance of HIV testing services (HTS) in HIV control, uptake of HTS among female sex workers (FSWs) across sub-Saharan Africa (SSA) remains sub optimal. Concerns about stigma associated with sex work and fear of loss of livelihood if HIV status becomes known, are some of the restrictions for FSWs to utilize HTS offered through health care … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…1517,19,21,22 Confidentiality is one of the advantages of HIVST, which was found in almost all perception analyses among female sex workers. 17,19,23 HIVST can help reduce the fear of a confidentiality breach by providers and through peer gossip. 23 In addition, women value perceived empowerment and self-responsibility as a benefit of choosing when and where to test and seek care, as described elsewhere.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1517,19,21,22 Confidentiality is one of the advantages of HIVST, which was found in almost all perception analyses among female sex workers. 17,19,23 HIVST can help reduce the fear of a confidentiality breach by providers and through peer gossip. 23 In addition, women value perceived empowerment and self-responsibility as a benefit of choosing when and where to test and seek care, as described elsewhere.…”
Section: Discussionmentioning
confidence: 98%
“…As described elsewhere, this study found the perceived benefits of saving time and financial resources related to transportation costs to facilities. 17,21,23 The oral fluid-based nature of the test, as opposed to bloodbased, was also seen as an advantage in this study, as it was in most studies among key populations. 24,25 The reluctance toward oral testing expressed in one focus group in this study is justified because female sex workers were familiar with using blood tests.…”
Section: Female Sex Workers' Perceptions Of Hivstmentioning
confidence: 91%
See 1 more Smart Citation
“…The more the diverse sources of social support, the more the FSWs are likely to seek care including routine HIV testing. This underscores the need for strengthened programmatic and sustained peer to peer support among female sex workers, an intervention that has been proven to support increased access to HIV services among FSWs (14,42) yet largely dependent on external funding with little funds allocation from governments (43) . As such, predictable program financing for sex work broader HIV prevention programs including financing community support systems and behaviour change communications where feasible, is a strong pillar for sustained support for FSWs HIV testing programs.…”
Section: Factorsmentioning
confidence: 99%
“…Indeed, for every 10 African men who are HIV-positive, there are 12 to 13 infected women; moreover, 55% of adults who acquire HIV are women, with profound implications for mother-to-child transmission [10]. In consonance with this fact, a greater number of women participate and work on HIV care programs in Africa, and a large proportion of the clinicoepidemiological investigations in these settings are based on care program data [52].…”
Section: High Degree Of International Collaboration Low Level Of Leamentioning
confidence: 99%